Indians Illustrated : The Image of Native Americans in the Pictorial Press - Coward, John M. (Book collections on Project MUSE., 2016)
"Indians Illustrated is a social and cultural history of Indian illustrations in Frank Leslie's Illustrated Newspaper, Harper's Weekly, and other illustrated journals during the last half of the nineteenth century, the heyday of the American pictorial press. The pictorial press era, spurred in the mid-1850s by the transportation revolution, innovations in printing technology, and an expanded literary and pictorial market, was marked by a proliferation of detailed, realistic woodblock engravings, pictures of newsworthy people and interesting events from across the nation and the world. The pictorial press frequently depicted Indians and Indian life in popular but narrowly conceived ways. In pictures, Indians were simplified and presented in familiar and easily understood categories, usually as variations on the 'good' Indian/'bad' Indian stereotypes long established in Euro-American culture. Indian men were depicted as 'tall and copper-colored, with braided hair, clothed in buckskin, and moccasins, and adorned in headdresses, beadwork and/or turquoise' while Indian women were depicted as either Indian princesses or squaws. John Coward argues that these pictures helped create and sustain a host of popular ideas and attitudes about Indians, especially ideas about the way Indians were supposed to look and act. By describing and analyzing the various themes and visual tropes across the years of the illustrated press, this book provides a deeper understanding of the racial codes and visual signs that white Americans used to represent Native Americans in an era of western expansion and Manifest Destiny"--Provided by publisher.